Adiponectin Attenuates Lipopolysaccharide-induced Apoptosis by Regulating the Cx43/PI3K/AKT Pathway - Liu, Luqian; Yan, Meijuan; Yang, Rui; Qin, Xuqing; Chen, Ling; Li, Li; Si, Junqiang; Li, Xinzhi; Ma, Ketao (Frontiers in Pharmacology, 2021)
Cardiomyocyte apoptosis is a crucial factor leading to myocardial dysfunction. Adiponectin (APN) has a cardiomyocyte-protective impact. Studies have shown that the connexin43 (Cx43) and phosphatidylinositol-3-kinase (PI3K)/protein kinase B (AKT) signaling pathways play an important role in the heart, but whether APN plays a protective role by regulating these pathways is unclear. Our study aimed to confirm whether APN protects against lipopolysaccharide (LPS)-induced cardiomyocyte apoptosis and to explore whether it plays an important role through regulating the Cx43 and PI3K/AKT signaling pathways. In addition, our research aimed to explore the relationship between the Cx43 and PI3K/AKT signaling pathways. In vitro experiments: Before H9c2 cells were treated with LPS for 24 h, they were pre-treated with APN for 2 h. The cytotoxic effect of APN on H9c2 cells was evaluated by a CCK-8 assay. The protein levels of Bax, Bcl2, cleaved caspase-3, cleaved caspase-9, Cx43, PI3K, p-PI3K, AKT and p-AKT were evaluated by Western blot analysis, and the apoptosis rate was evaluated by flow cytometry. APN attenuated the cytotoxicity induced by LPS. LPS upregulated Bax, cleaved caspase-3 and cleaved caspase-9 and downregulated Bcl2 in H9c2 cells; however, these effects were attenuated by APN. In addition, LPS upregulated Cx43 expression, and APN downregulated Cx43 expression and activated the PI3K/AKT signaling pathway. LPS induced apoptosis and inhibited PI3K/AKT signaling pathway in H9c2 cells, and these effects were attenuated by Gap26 (a Cx43 inhibitor). Moreover, the preservation of APN expression was reversed by LY294002 (a PI3K/AKT signaling pathway inhibitor). In vivo experiments: In C57BL/6J mice, a sepsis model was established by intraperitoneal injection of LPS, and APN was injected into enterocoelia. The protein levels of Bax, Bcl2, cleaved caspase-3, and Cx43 were evaluated by Western blot analysis, and immunohistochemistry was used to detect Cx43 expression and localization in myocardial tissue. LPS upregulated Bax and cleaved caspase-3 and downregulated Bcl2 in sepsis; however, these effects were attenuated by APN. In addition, the expression of Cx43 was upregulated in septic myocardial tissue, and APN downregulated Cx43 expression in septic myocardial tissue. In conclusion, both in vitro and in vivo, the data demonstrated that APN can protect against LPS-induced apoptosis during sepsis by modifying the Cx43 and PI3K/AKT signaling pathways.